Analisis Kadar Karboksihemoglobin (COHb) pada Montir Motor di Area Kota Samarinda - Rifky Saldi A. Wahid; Georgius Kaperius; La Ode Akbar Rasydy (Jaringan Laboratorium Medis, 2023)
The quality of air is very important for the environment and human life, however, along with developments in today's increasingly developed and modern era, the quality of the air itself is getting worse and the substances that become air pollutants, one of which is carbon monoxide. Exposure to high amounts of carbon monoxide gas over a continuous exposure period can of course increase carboxyhemoglobin levels in the blood, which will cause health problems. To determine the relationship between carboxyhemoglobin levels in the blood of motor vehicle mechanic workers in the Samarinda city area based on factors such as age, length of work, length of service, and smoking habits. This research used a cross sectional analytical survey design, and sample measurements used the Hindsberg-Lang method which was carried out in May 2023 with a sample size of 17 people and a Spearman rank statistical test was carried out to see whether there was a relationship between variables. 17 motor vehicle mechanics had COHb concentrations that exceeded the normal limit of 3.5%, where the lowest carboxyhemoglobin level was 6.10% and the highest was 9.64%. Correlation data obtained from the p value of age (p=0.000), length of service (p=0.000), time worked (p=0.000), and smoking habits (p=0.004) on COHb levels in the blood of motor vehicle mechanics. The Conclusion: COHb levels in motor vehicle mechanics are above 3.5% and there is a significant relationship between age, length of service, working time and smoking habits on COHb levels in the blood of motor vehicle mechanics.